Analisis Pengendalian Persediaan Bahan Baku Dalam Perencanaan Proses Produksi Pada Pabrik Tahu Ambon - Musaid, Sri Astuti Musaid; Kesaulya, Juliana (Journal of Applied Accounting, 2023)
This study aims to determine the control of soybean raw material inventory applied at the Ambon Tofu Factory and to determine the number of economic soybean raw material inventory orders at the Ambon Tofu Factory. The type of research used in this research is comparative descriptive method research. The data processed is in the form of inventory reports on the purchase and use of soybean raw materials at the Ambon Tofu Factory in 2017. The data analysis techniques used in this study are EOQ, Safety stock, and ROP. Based on the results of research using the EOQ method, the economic ordering amount of soybean raw materials are obtained at 10,480 kg, with a frequency of ordering 17 times, safety stock of 7,221 kg, ROP can be done when the soybean raw material in the warehouse is 1,497 kg, and the total inventory cost is Rp. 335,352. The conclusion of this study shows that the application of the Economic Order Quantity (EOQ) method shows a more economical number of orders to minimize the costs incurred at the tofu factory and can maximize the profit earned. Keywords: raw material control, economic order quantity (EOQ)